Greening effect in slag cement materials. (November 2017) - Le Cornec, Domitille; Wang, Qirong; Galoisy, Laurence; Renaudin, Guillaume; Izoret, Laurent; Calas, Georges
Abstract: This article presents the first spectroscopic data describing the processes responsible for the temporary blue-green coloration that forms during the hydration of various materials containing Ground Granulated Blast-furnace Slag (GGBS) under anoxic conditions. UV-visible-near infrared Diffuse Reflectance (DR) spectra demonstrate a striking similarity of the coloring center forming during the curing of a broad range of GGBS-bearing materials (pure GGBS with different compositions, mix Portland cement/GGBS (30/70), concrete and mortar). All spectra are similar to those of polysulfide complexes contained in the interlayer spacing of a synthetic green-colored hydrated calcium aluminate phase (AFm). This "greening effect" demonstrates a progressive oxidation of sulfide-based compounds initially contained in these materials during curing of GGBS bearing materials.